Pengaruh Modernisasi Perpajakan, Sosialisasi dan Kesadaran terhadap Kepatuhan Wajib Pajak dengan Tingkat Pendapatan sebagai Variabel Moderasi : (Studi Kasus Kendaraan Bermotor di Kota Bekasi) - Vina Hariyati; Nera Marinda Machdar; Cahyadi Husadha (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to examine the Effect of Modernization of Tax Administration System, Tax Socialization and Tax Behavior Awareness on Taxpayer Compliance with Income Level as Moderation Variable. This researcher uses primary data by distributing questionnaires to two-wheeled motor vehicle taxpayers at Samsat Bekasi City. The determination of the sample in this study used the purposive sampling method. The Population in this study was 100 taxpayers. This study uses Smart PLS 3.0 Software. The results of this study indicate that modernization of the tax administration system and tax socialization have no effect on taxpayer compliance. While tax behavior awareness has a positive and significant effect on taxpayer compliance. Income level cannot moderate the effect of modernization of the tax administration system, tax socialization and tax behavior awareness on taxpayer compliance.